Enabling Process Improvement Through Production Process Mapping : A Case Study for a Finnish Manufacturing Company - Myllykangas, Jani (My University, 2025)
Many Finnish small and medium sized enterprises (SME’s) operate with unmapped, informalized or poorly defined manufacturing processes. Unmapped or unclear production processes with insufficient process transparency can act as a barrier that limits companies’ productivity and scalability, and can impede process improvement efforts, such as process automation. Process mapping is a foundational work for many organizations seeking to build business process management competencies within the organization, and in many cases can serve as basis for future operational improvement efforts, such as implementing lean manufacturing practices or the theory of constraints. By mapping or formalizing production processes, businesses can increase process transparency and process-based understanding among the workers, facilitate effective communication be-tween management and workers, reinforce process-based thinking and reduce change resistance among workers that can otherwise inhibit or slow down companies’ efforts to improve their manufacturing processes and operations. Addressing unmapped manufacturing processes is therefore critical to enable businesses to pursue principles such as lean manufacturing, theory of constraints, continuous improvement, and in general to improve the company’s operational effi-ciency and to strengthen their competitive advantages in the markets. This study focuses on mapping the production processes for a real Finnish case company that operates in the metal industry. The research was conducted using qualitative research method-ology. Semi-structured interviews were used as the primary method of data collection, comple-mented by observations made during factory tours, and existing documentations provided by the case company. Team leaders from five different production departments were interviewed at the case company. In addition, the chief of production, and the chief of production planning from the production planning department were also interviewed. Thematic analysis was used to analyze the collected data. Based on the data analysis, the key process steps, material flows and information flows were identified, and their interrelations were mapped using swim lane diagramming methodology. In addition, process descriptions were prepared for each production department, providing a gen-eral description of key process steps, and for the responsibilities of the team leaders and the operators of the departments.

Monet Suomalaiset pienet ja keskisuuret yritykset (pk-yritykset) operoivat kartoittamattomilla, epävirallisilla tai huonosti määritellyillä tuotantoprosesseilla. Kartoittamattomat tai epäselvät tuotantoprosessit, joissa ei ole riittävää läpinäkyvyyttä, voivat toimia esteenä, joka rajoittaa yritysten tuottavuutta ja skaalautuvuutta ja voi hankaloittaa prosessien kehittämistoimia, kuten prosessien automointia. Prosessien kartoitus on pohjustavaa työtä monille organisaatioille, jotka pyrkivät rakentamaan liiketoimintaprosessien hallinnan osaamista, ja se voi monissa tapauksissa toimia lähtökohtana tuleville toiminnan parantamistoimille, kuten lean-tuotannonkäytäntöjen tai rajoitteiden teorian (Theory of Constraints) soveltamiselle. Tuotantoprosessien kartoittamisen tai määrittelyn avulla yritykset voivat lisätä prosessien lä-pinäkyvyyttä ja prosessipohjaista ymmärrystä työntekijöiden keskuudessa, edistää tehokasta viestintää johdon ja työntekijöiden välillä, vahvistaa prosessikeskeistä ajattelua ja vähentää muu-tosvastarintaa, joka muuten voisi estää tai hidastaa yritysten pyrkimyksiä kehittää tuotantopro-sessejaan ja toimintaansa. Kartoittamattomien tuotantoprosessien käsittely on siksi kriittistä, jotta yritykset voivat soveltaa lean-tuotannon, rajoitteiden teorian ja jatkuvan parantamisen periaatteita, sekä yleisesti ottaen parantaa toiminnan tehokkuutta ja vahvistaa kilpailuetujaan markkinoilla. Tämä tutkimus keskittyy tuotantoprosessien kartoittamiseen Suomalaisessa metalliteollisuudessa toimivassa yrityksessä. Tutkimus toteutettiin käyttämällä laadullista tutkimusmenetelmää. Ensisi-jaisena tiedonkeruumenetelmänä käytettiin puolistrukturoituja haastatteluja, joita täydensi teh-daskierroksilla tehdyt havainnot sekä yrityksen toimittamat olemassa olevat dokumentit. Työssä haastateltiin yrityksen viiden eri tuotanto-osaston tiimiesihenkilöitä. Lisäksi haastateltiin tuotantopäällikköä, sekä tuotannonsuunnitteluosaston tuotannon suunnittelupäällikköä. Kerätty-jen tietojen analysoinnissa käytettiin temaattisen analyysin menetelmää. Analyysin perusteella tunnistettiin keskeiset prosessivaiheet, materiaali- ja informaatiovirrat, ja niiden väliset suhteet, ja ne kartoitettiin swim lane-kaaviomenetelmällä. Lisäksi laadittiin proses-sikuvaukset kullekin tuotanto-osastolle, joissa esitettiin yleinen kuvaus keskeisistä prosessivai-heista sekä tiimiesihenkilöiden ja osastojen operaattoreiden vastuista.
Keywords: production planning; production control; process control; mapping; information flows; manufacturing industry; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management